The influence of using animated videos on elementary school students' learning motivation - Desri Elvia Yani; Putri Octa Hadiyanti (Himpunan Pengembang Kurikulum Indonesia, 2025)
The low learning motivation of students in learning science in elementary schools is a challenge that needs to be overcome through appropriate learning media to be used in the learning process. This study aims to determine the effect of using animated video media of the solar system on the learning motivation of SD Negeri 005 Kabun grade VI students. The approach used in this study is quantitative with a quasi-experimental method in the form of a nonequivalent control group design. The sample consisted of a control class of 19 students and an experimental class of 18 students. Data were collected through a questionnaire and analyzed using an independent sample t-test. The study's results showed a significant effect of the use of animated videos in learning science, especially the solar system material, on students' learning motivation. This is indicated by the increased attention, interest, and activeness of students in the experimental class compared to the control class. Based on these findings, it is recommended for teachers to be able to utilize animated video media as a learning aid to increase student motivation and involvement in the teaching and learning process. Abstrak Rendahnya motivasi belajar peserta didik dalam pembelajaran IPAS di sekolah dasar menjadi tantangan yang perlu diatasi melalui media pembelajaran yang tepat untuk digunakan dalam proses pembelajaran. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media video animasi sistem tata surya terhadap motivasi belajar peserta didik kelas VI SD Negeri 005 Kabun. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif dengan metode desain quasi experimental berbentuk nonequivalent control group. Sampel terdiri dari kelas kontrol sebanyak 19 orang peserta didik dan kelas eksperimen sebanyak 18 orang peserta didik. Data dikumpulkan melalui angket kuesioner dan dianalisis menggunakan uji independent sample t-test. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan dari penggunaan video animasi dalam pembelajaran IPAS khususnya materi sistem tata surya terhadap motivasi belajar peserta didik. Hal ini ditunjukkan dengan meningkatnya perhatian, minat, dan keaktifan peserta didik pada kelas eksperimen dibandingkan dengan kelas kontrol. Berdasarkan hasil temuan tersebut, disarankan bagi para guru agar dapat memanfaatkan media video animasi sebagai alat bantu pembelajaran untuk meningkatkan motivasi serta keterlibatan peserta didik dalam proses belajar mengajar. Kata Kunci: motivasi peserta didik; media pembelajaran; sekolah dasar; sistem tata surya; video animasi